Determinación de la topología membranal de la proteína ChrA de Pseudomonas aeruginosa - Jiménez Mejía, Rafael (Universidad Michoacana de San Nicolás de Hidalgo, 2005)
The P. aeruginosa ChrA protein of 416 amino acids has been characterized at the functional level and was determined to function as a transporter that expels the cytoplasm chromate; however, only structural information of the amino terminal region of the protein is available, so the objective of this work was to determine the membrane topology of this transporter using translational fusions with the reporter genes phoA (alkaline phosphatase) and lacZ (β -galactosidase). For this, the binary E. coli-Pseudomonas pUCPphoA and pUCPlacZ binary expression vectors were constructed and 16 fusions were made in each of these vectors. Fusions with each of the reporter proteins were located in different hydrophilic regions of the protein. Reporters' enzymatic activity was determined in E. coli and P. aeruginosa, with very similar results. Fusions located in amino acids Ala188, Val233, Ala310, and Pro413 showed only PhoA activity which indicates that the regions where these residues are located are located in the periplasm, while fusions in amino acids Ile159, Phe263, Asp276, Ala334 and Asn393 only produced LacZ activity, indicating that the hydrophilic handles where these amino acids are found are located the cytoplasm. Fusions in amino acids Glu369 and Gly416 produced enzymatic activity of the two reporter proteins and these regions were located in the peripasma. With the fusions in amino acids Leu99, Val152, Asp162, Gly305 and Met313, no activity was obtained from any of the enzymes, suggesting that these amino acids are in a transmembrane segment (STM). The results obtained in this work do not match the previously proposed topological model for ChrA of 12 STM and are consistent with a topological model of 13 STM.

La proteína ChrA de P. aeruginosa de 416 aminoácidos ha sido caracterizada a nivel funcional y se determinó que funciona como un transportador que expulsa el cromato del citoplasma; sin embargo, sólo se cuenta con información estructural de la región amino terminal de la proteína, por lo que el objetivo de este trabajo fue determinar la topología membranal de este transportador utilizando fusiones traduccionales con los genes reporteros phoA (fosfatasa alcalina) y lacZ (β-galactosidasa). Para ello se construyeron los vectores de expresión binarios E. coli-Pseudomonas pUCPphoA y pUCPlacZ y se hicieron 16 fusiones en cada uno de estos vectores. Las fusiones con cada una de las proteínas reporteras se localizaron en diferentes regiones hidrofílicas de la proteína. La determinación de la actividad enzimática de los reporteros se hizo en E. coli y en P. aeruginosa, con resultados muy similares. Las fusiones localizadas en los aminoácidos Ala188, Val233, Ala310, y Pro413 sólo mostraron actividad de PhoA lo cual indica que las regiones donde se encuentran estos residuos se localizan en el periplasma, mientras que las fusiones en los aminoácidos Ile159, Phe263, Asp276, Ala334 y Asn393 sólo produjeron actividad de LacZ, indicando que las asas hidrofílicas donde se encuentran estos aminoácidos se localizan el citoplasma. Las fusiones en los aminoácidos Glu369 y Gly416 produjeron actividad enzimática de las dos proteínas reporteras y estas regiones fueron localizadas en el peripasma. Con las fusiones en los aminoácidos Leu99, Val152, Asp162, Gly305 y Met313 no se obtuvo actividad de ninguna de las enzimas, lo que sugiere que estos aminoácidos están en un segmento transmembranal (STM). Los resultados obtenidos en este trabajo no concuerdan con el modelo topológico previo propuesto para ChrA de 12 STM y son consistentes con un modelo topológico de 13 STM.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2005-0003; Proteínas; Áminoácidos; Enzimas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3814